Dynamics of Madrasah and Implementation System Excellent Islamic Education - Aslamiyah, Nurul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
implementing excellent Islamic education in Indonesia. Using a descriptive qualitative method with a literature study approach, this study examines data from various scientific sources, official policies, and educational documents. The data collection technique is carried out through thematic documentation, while the analysis is carried out by content analysis technique. The results of the study show that madrassas have undergone significant transformation since the colonial period to the era of the Independent Curriculum. Several important policies, such as the Decree of the Three Ministers, the MAPK program, the 2013 Curriculum, and the Independent Curriculum became milestones in Islamic education reform. Despite progress, challenges such as inequality in human resources, limited infrastructure, and suboptimal management still hinder the delivery of excellent Islamic education. The research concludes that the reformulation of the madrasah system needs to be carried out through a participatory management approach, the application of the principle of total quality education, and the strengthening of the local context and Islamic values. The results of this study are expected to be a reference in designing Islamic education policies that are more adaptive, inclusive, and sustainable.